Family, Work, And Memories: A study in the City of Ivoti (RS) with women older than 60 years old - Anschau, Berlize Regina Elias (2015)
This study aimed to understand which family influences lead elderly women to remain active in the labor market. The study design is qualitative, exploratory and cross sectional. The 8 participants underwent a semi structured interview. The data were submitted to Bardin content analysis. The results showed strong family influence in the process of entering and remaining in the labor market, producing benefits beyond the economic dimension.